The Effect of Workload on Cyberloafing with Burnout As A Mediating Variable in Employees of PT. XYZ - Trimega Mimika Onibala; I Gusti Made Suwandana (Return : Study of Management, Economic and Bussines, 2025)
The internet and social media are now an essential part of life, with employees considering the internet as a primary need aided by companies providing Wi-Fi facilities and internet-connected electronics to support work. This study aims to analyze the influence of workload on cyberloafing with burnout as a mediating variable in employees. Cyberloafing is a behavior that uses electronic devices during work hours that are not related to work. High work pressure in the company can cause employees to feel burnout, which is emotional exhaustion due to individuals facing workloads. The study is based on the Social Exchange Theory, which explains that the reciprocal relationship between individuals and organizations can influence work behavior. A high workload has the potential to trigger burnout, which is a state of emotional exhaustion due to individuals facing high work pressure, which can ultimately encourage cyberloafing as a stress diversion mechanism. The approach used is a quantitative approach with a survey method through a questionnaire that is distributed to all employees. Data analysis was carried out using the Path Analysis technique with the help of SPSS. The results show that workload has a significant positive effect on burnout, which in turn has a significant positive effect on cyberloafing, and burnout acts as a significant mediating variable between workload and cyberloafing, so that workload is not only directly but also indirectly affected through burnout. The implications of this study are the importance of paying attention to employee workload and trying to reduce burnout factors as well as implementing clear internet usage policies and providing training on internet use ethics and time management, which is expected to contribute to the development of management science, especially in the field of human resource management and organizational behavior.